2007
DOI: 10.1063/1.2710223
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory thermal expansion of Pb thin films modulated by quantum size effects

Abstract: Varied temperature photoemission study is performed to investigate the quantum size effects on the thermal property of atomically flat Pb films grown on Si͑111͒. The binding energies of the quantum well states for the films with thicknesses from 10 to 24 ML exhibit a linear increase with increasing temperature from 75 to 270 K. Under free electron approximation, thermal expansion coefficients of the thin films are determined, which manifest a large enhancement and oscillation behavior. The large enhancement is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…As a result, the quantum oscillations in superconducting transition temperature T c were observed, which correlate perfectly with the confined electronic structure. 36) Other novel properties induced by QWS, such as double-layer growth, [29][30][31]38) selective strip-flow growth and growth rate modulation, 39) oscillating perpendicular upper critical field, 40) thermal expansion, 41) adhesion force, 42) local work function (LWF), 43) and surface diffusion barrier, 44) have also been observed. In this article, we would mainly summarize these recent results on Pb/Si(111) by our group.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the quantum oscillations in superconducting transition temperature T c were observed, which correlate perfectly with the confined electronic structure. 36) Other novel properties induced by QWS, such as double-layer growth, [29][30][31]38) selective strip-flow growth and growth rate modulation, 39) oscillating perpendicular upper critical field, 40) thermal expansion, 41) adhesion force, 42) local work function (LWF), 43) and surface diffusion barrier, 44) have also been observed. In this article, we would mainly summarize these recent results on Pb/Si(111) by our group.…”
Section: Introductionmentioning
confidence: 99%
“…More interestingly, the anisotropy of the m-band of a Pb film is smaller than for the band of the bulk, the reason for which needs more detailed studies. We can explain very strong thickness-dependent physical properties observed in Pb thin films [5][6][7][8][9][10][11][12][13][14][15][16][17] in terms of the 1-D-like DOS singularity developing from the 2-D band bending: it is simply because the electronic structure near EF is now dominated by the singularity. Although we have only studied 23 and 24 ML Pb films, we know where the VHS of other Pb films is from previous STS measurements [16].…”
Section: (D) and 4(e)mentioning
confidence: 99%
“…These strong oscillations in the properties of thick Pb films are very puzzling since, according to theory, the quantum size effect should quickly become damped with increasing thickness [18]. The electronic structure of Pb films with different thicknesses has been studied by photoemission spectroscopy and scanning tunneling spectroscopy (STS) [5,12,[14][15][16]. Many of these studies have revealed that the oscillations in the DOS at E F are consistent with the observed properties of the films-for instance, higher superconducting transition temperature (T c ) [5], surface reactivity [15] and Kondo temperature [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations